The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1002/cctc.201701503
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Confined Synthesis of Ti4O7 Supported Platinum Electrocatalysts with Enhanced Activity and Stability for the Oxygen Reduction Reaction

Abstract: Herein, an in situ confined synthesis of highly conductive titanium oxide supported Pt catalysts is successfully employed. The method involves crystallization and formation of TiO2 particles inside the inert silica shell introduced by using hexamethyldisilazane (HMDS). The conductivity of titania is found to be greatly enhanced by increased annealing temperature, whereas the inevitable decrease in the specific surface area was effectively inhibited by the confining silica shell derived from HMDS. The optimal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 63 publications
1
8
0
Order By: Relevance
“…A known drawback of TiO 2 is its poor conductivity . To resolve this, several studies have demonstrated that the conductivity of TiO 2 can be enhanced through the reduction of metal oxides to form oxygen vacancies, which can be achieved through high‐temperature annealing in reducing atmospheres to obtain Magnéli phased TiO 2 possessing conductivities several orders higher than TiO 2 (e.g., Ti 3 O 5 [530 S/cm], Ti 4 O 7 [1035 S/cm], Ti 5 O 9 [631 S/cm], Ti 6 O 11 [63 S/cm], Ti 8 O 15 [25 S/cm], Ti 3 O 5 + Ti 4 O 7 [410 S/cm], Ti 4 O 7 + Ti 5 O 9 [330 S/cm], and Ti 5 O 9 + Ti 6 O 11 [500 S/cm]) . Here, researchers reported that the most conductive phase of titanium was Ti 4 O 7 , which reached its optimal conductivity at ca.…”
Section: Approaches To Enhancing the Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…A known drawback of TiO 2 is its poor conductivity . To resolve this, several studies have demonstrated that the conductivity of TiO 2 can be enhanced through the reduction of metal oxides to form oxygen vacancies, which can be achieved through high‐temperature annealing in reducing atmospheres to obtain Magnéli phased TiO 2 possessing conductivities several orders higher than TiO 2 (e.g., Ti 3 O 5 [530 S/cm], Ti 4 O 7 [1035 S/cm], Ti 5 O 9 [631 S/cm], Ti 6 O 11 [63 S/cm], Ti 8 O 15 [25 S/cm], Ti 3 O 5 + Ti 4 O 7 [410 S/cm], Ti 4 O 7 + Ti 5 O 9 [330 S/cm], and Ti 5 O 9 + Ti 6 O 11 [500 S/cm]) . Here, researchers reported that the most conductive phase of titanium was Ti 4 O 7 , which reached its optimal conductivity at ca.…”
Section: Approaches To Enhancing the Activitymentioning
confidence: 99%
“…10 3 S/cm at room temperature . However, researchers also reported that this method can lead to low surface areas and cause poor dispersion and increased aggregation of NPs during the blending of the catalyst with the support, presenting a dilemma between the need for high conductivity and the need for high surface area for the electrocatalyst and support. Another method to enhance the conductivity of TiO 2 is through the introduction of appropriate donor dopants such as Nb, Mo, and W, which can achieve relatively better conductivities as compared with bare TiO 2 .…”
Section: Approaches To Enhancing the Activitymentioning
confidence: 99%
“…Although carbon with a higher graphitization degree has higher corrosion resistance versus carbon black, it is still inadequate to mitigate its corrosion under long-term operation due to its intrinsic carbon composition. Therefore, to improve PEMFCs catalyst support stability, considerable work has been done over the past few decades on non-carbon support materials [19][20][21][22][23][24], including oxides, carbides, and nitrides. However, the improvements are insufficient to prevent performance loss under highly oxidative conditions during automotive start-stop cycles.…”
Section: Introductionmentioning
confidence: 99%
“…27 Many studies have shown that the interaction between Pt and titanium-oxide-based supports enhance both the mass activity (MA) and durability of Pt. 18,24,[26][27][28][29][30][31][32][33][34] In our previous study on a microporous Ti 6 O 11 support, Pt nanoparticles were deposited it using the coaxial arc plasma deposition (APD) method. Owing to the high energy applied for Pt vaporization, Pt nanoparticles deposited by APD possess unique properties, such as controllable particle size, 35,36 high activity, 37,38 and high durability.…”
Section: Introductionmentioning
confidence: 99%